Comparison of information and communication technology contribution on newly industrialized countries'economic growth - Maryam Farhadi,; Rahmah Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2012)
In recent years, progress in information and communication technology (ICT) has coused many structural changes, including the reorganization of economics globalization, and trade extention,which has led to capital flows and the enhancement of information availability.Moreover,ICT plays a significant role in the development of each economic sector,especially during liberazation processes. Growth economists predict that economic growth is driven by investment in ICT.However, empirical studies on this issue have produced mixed results, due to different research methodology and geographical configuration ultilized in the studies, In this paper we estimate the endogenous production growth model, using panel data of the newly industrialized countries (NICS) in Asia-namely Singapore, South Korea, Hong Kong, and Malaysia- over the period of 1990-2007. We find a strong significant positive impact of ICT investment on economic growth for these countries.This indicates that if these countries seek to enhance their economic growth, they need to omplement specific policies that facilitate investment in ICT.